Composite material and preparation method thereof

By using the combination technology of waste fabric layer and starch adhesive, the problems of high production costs of traditional composite materials and epoxy resin brittleness are solved, and the high-value reuse of waste fabrics and the impact resistance of composite materials are improved.

CN119871934APending Publication Date: 2025-04-25BEIJING INST OF CLOTHING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional protective composite materials have high production costs, the brittleness of epoxy resins limits their flexibility and impact resistance, and their non-degradability poses a burden to the environment.

Method used

Use a waste fabric layer as the base material, and it is laid and cured layer by layer through starch adhesive to form a composite material.

Benefits of technology

The recycling and reuse of waste fabrics is realized, production costs are reduced, and the impact resistance and environmental protection of composite materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871934A_ABST
    Figure CN119871934A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof. The preparation method comprises the following steps: obtaining a waste fabric layer; preparing starch into a starch adhesive; laying the waste fabric layers to a preset thickness layer by layer, and enabling the starch adhesive to permeate into each waste fabric layer to obtain a preformed body; and curing the preformed body to obtain the composite material. According to the preparation method disclosed by the invention, the waste fabric layer is used as a base material of the composite material, so that the recycling of the waste fabric is realized, the resource waste is reduced, and the concept of circular economy is met. Therefore, not only is the demand on new raw materials reduced, but also the pressure of the waste fabric on the environment is relieved, and high-valued reutilization of the waste fabric can be realized. And the starch adhesive is used as the adhesive for bonding the waste fabric layer, so that the production cost of the composite material can be greatly reduced, the composite material is more suitable for large-scale production, and the weight content of the fabric in the composite material is increased, thereby reducing the weight of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective materials, and specifically relates to a composite material and a preparation method thereof. Background Art

[0002] Traditional protective composite materials are usually prepared using fabrics and chemical adhesives such as epoxy resins. Although epoxy resins provide good bonding strength, their inherent brittleness limits the flexibility and impact resistance of the composites. In addition, the high production cost of epoxy resins is not conducive to large-scale applications, and their relatively large weight is not conducive to the lightweighting of composite materials. More importantly, the non-degradability of epoxy resin adhesives has imposed a long-term burden on the environment and is not conducive to sustainable development.

[0003] At the same time, the textile industry is facing huge environmental and resource challenges in the context of the national climate posing a major threat to human society. The global recycling rate of waste textiles is only 15%, and most of the waste textiles that have not been recycled are often incinerated with urban garbage, which not only causes a huge waste of resources, but also aggravates environmental pollution problems. Summary of the invention

[0004] The purpose of the present invention is to provide a new technical solution for a method for preparing a composite material, which can at least solve the technical problem of high production cost of existing composite materials.

[0005] According to a first aspect of the present invention, there is provided a method for preparing a composite material, comprising:

[0006] Obtain scrap fabric layers;

[0007] preparing starch into starch adhesive;

[0008] Laying the waste fabric layers layer by layer to a preset thickness, and allowing the starch adhesive to penetrate each of the waste fabric layers to obtain a preform;

[0009] The preform is cured to obtain a composite material.

[0010] Optionally, the method for obtaining the waste fabric layer includes:

[0011] Wash and dry waste fabrics;

[0012] The waste fabric is cut into a predetermined size to obtain a waste fabric layer.

[0013] Optionally, before cutting the waste fabric, the material and / or structure of the waste fabric is detected, and waste fabric of predetermined material and / or structure is screened out according to the detection result, and the waste fabric of predetermined material and / or structure is cut to a predetermined size to obtain a waste fabric layer.

[0014] Optionally, the method for preparing starch as a starch adhesive comprises:

[0015] Mixing water and an acidic reagent to obtain a mixed solution;

[0016] Mixing starch with the mixed solution to obtain a first mixed substance;

[0017] mixing the first mixed substance with alum and / or glucose to obtain a second mixed substance;

[0018] The second mixed material is heated and boiled to obtain a starch adhesive.

[0019] Optionally, the mixed solution is added to the starch in portions and stirred continuously during the whole process; and / or, stirring is continuously performed during the heating of the second mixed substance.

[0020] Optionally, glycerin and salicylic acid alcohol solution are added to the second mixed substance.

[0021] Optionally, the temperature of heating the second mixed substance is 50°C to 80°C.

[0022] Optionally, the weight ratio of the starch to the water is 1:2-7, the weight ratio of the starch to the acidic agent is 100:2-5, and the weight ratio of the starch to the alum is 100:10-30.

[0023] Optionally, in the process of stacking the waste fabric layers layer by layer, the stacking direction of at least one layer of waste fabric is different from or the same as the stacking direction of the previous layer.

[0024] Optionally, the method of curing the preform to obtain a composite material comprises:

[0025] Applying pressure to the preform and allowing it to stand and solidify to form a solidified molded body;

[0026] The cured molded body is heated and dried to obtain a composite material.

[0027] Optionally, in the composite material, the content of the waste fabric layer is 79wt.% to 91wt.%.

[0028] Optionally, in the composite material, the content of the waste fabric layer is 87 wt.%.

[0029] Optionally, the starch is one or more combinations of wheat flour, rice flour, corn flour, glutinous rice flour, sweet potato flour, and lotus root flour.

[0030] The present invention also provides a composite material, which is made by any of the above-mentioned preparation methods.

[0031] According to the preparation method of the composite material of the present invention, the waste fabric layer is used as the base material of the composite material, so that the waste fabric can be recycled and reused, and the waste of resources can be reduced, which is in line with the concept of circular economy. This not only reduces the demand for new raw materials, but also reduces the pressure on the environment caused by waste fabrics, and can achieve high-value reuse of waste fabrics. In addition, the use of starch adhesive as an adhesive for bonding the waste fabric layer can greatly reduce the production cost of the composite material, making it more suitable for large-scale production, and increase the weight content of the fabric in the composite material, thereby reducing the weight of the composite material; and effectively improves the strength of the composite material, improves the flexibility of the composite material, thereby effectively improving the impact resistance of the composite material, so that the composite material can withstand greater impact force; at the same time, the green and environmentally friendly characteristics of the starch adhesive also enhance the environmental protection of the composite material.

[0032] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0034] Figure 1 is a flow chart of a method for preparing a composite material according to an embodiment of the present invention;

[0035] Figure 2 The impact performance curves of composite materials with different waste fabric layer contents after impact; wherein, (a) is the force-time curve and (b) is the energy-time curve;

[0036] Figure 3 The impact performance curves of a composite material with a waste fabric layer content of 87wt.% after being impacted by different impact energies; wherein (a) is a force-time curve and (b) is an energy-time curve. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0038] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0039] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0040] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0041] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0042] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a composite material, and the method comprises: S100 to S400.

[0043] S100, obtaining a waste fabric layer;

[0044] That is to say, firstly, according to the application requirements of the composite material, large-sized waste fabrics of suitable corresponding fiber materials can be selected. For example, waste fabrics woven from wool fibers, aramid fibers, etc. can be selected. Then, the large-sized waste fabrics can be cut into waste fabric layers of the required size and quantity according to actual needs.

[0045] S200, preparing starch into a starch adhesive;

[0046] It should be noted that step S200 can be performed after the step of obtaining multiple waste fabric layers, or before or simultaneously with the step of obtaining multiple waste fabric layers, and the preparation order can be adjusted according to actual production conditions and needs.

[0047] S300, stacking the waste fabric layers layer by layer to a preset thickness, and allowing the starch adhesive to penetrate each of the waste fabric layers to obtain a preform;

[0048] Specifically, first prepare a smooth mold board of appropriate size, then lay waste fabric layers on the mold board layer by layer, and after each layer of waste fabric is laid, use a brush to evenly apply starch adhesive on the layer of fabric to ensure that the starch adhesive penetrates the waste fabric layer and expel all bubbles. Repeat this step until all waste fabric layers have been laid and coated with starch adhesive, and a preform can be formed.

[0049] S400, curing the preform to obtain a composite material.

[0050] That is to say, the starch adhesive in the preform can be transformed from liquid or semi-solid to solid through curing treatment, so that multiple layers of waste fabric are firmly bonded together by the starch adhesive to form a whole. After the starch adhesive is cured, the desired composite material can be obtained.

[0051] Therefore, according to the preparation method of the composite material of the embodiment of the present invention, the waste fabric layer is used as the base material of the composite material, so that the waste fabric is recycled and reused, the waste of resources is reduced, and it is in line with the concept of circular economy. This not only reduces the demand for new raw materials, but also reduces the pressure on the environment caused by waste fabrics, and can achieve high-value reuse of waste fabrics. In addition, the use of starch adhesive as an adhesive for bonding waste fabric layers can greatly reduce the production cost of the composite material, making it more suitable for large-scale production, and increase the weight content of the fabric in the composite material, thereby reducing the weight of the composite material; and effectively improve the strength of the composite material, improve the flexibility of the composite material, thereby effectively improving the impact resistance of the composite material, so that the composite material can withstand greater impact force; at the same time, the green and environmentally friendly characteristics of the starch adhesive also enhance the environmental protection of the composite material.

[0052] According to one embodiment of the present invention, the method for obtaining the waste fabric layer includes: S110 and S120.

[0053] S110, washing and drying waste fabrics;

[0054] S120, cutting the waste fabric into a predetermined size to obtain a waste fabric layer.

[0055] Specifically, the method for obtaining the waste fabric layer mainly includes: firstly, washing the waste fabric (for example, waste wool fabric), drying it in an electric constant temperature blast drying oven after washing, and then cutting the washed and dried waste fabric into a predetermined size to obtain the desired waste fabric layer.

[0056] In an optional example of the present invention, before cutting the waste fabric, the material and / or structure of the waste fabric is detected, and waste fabric of predetermined material and / or structure is screened out according to the detection result, and the waste fabric of predetermined material and / or structure is cut to a predetermined size to obtain a waste fabric layer.

[0057] That is to say, in order to ensure the controllability of the strength of the composite material, the waste fabrics can be classified, for example, they can be classified according to the material of the waste fabrics. Specifically, when detecting the material of the waste fabrics, the combustion method can be used for identification. The identification process is: take a small amount of the sample from the corresponding waste fabric, clamp it with tweezers, slowly approach the flame, and observe the reaction of the fiber to heat (such as melting, shrinkage). Move the sample into the flame, let it burn fully, and observe the burning of the fiber in the flame. Remove the sample from the flame and observe the burning state of the fiber after leaving the fire. When the flame of the sample goes out, smell it. After the sample cools down, observe the state of the residue and gently twist the residue with your hands. Finally, the material of the waste fabric can be determined according to various conditions. Alternatively, the identification can be done by microscopy. The identification process is as follows: the yarn is pulled out of the fabric, untwisted into a single fiber, and then aligned side by side, placed on a glass slide, glycerol or aniline is added (be careful not to introduce bubbles), a cover glass is placed, and the material of the waste fabric is determined by observing its morphology under appropriate magnification conditions and comparing it with standard photos or standard data; alternatively, the material of the waste fabric can be analyzed by Fourier infrared spectroscopy, that is, a beam of infrared light is irradiated on the fabric, and the molecules of the sample will absorb part of the light energy and convert it into vibrational energy and rotational energy of the molecules, thereby forming an infrared spectrum. Each characteristic absorption band in the infrared spectrum contains information about the groups and chemical bonds in the sample molecules. Different substances have different infrared spectra. By analyzing these spectral information, the material of the waste fabric can be determined.

[0058] In order to ensure the controllability of the strength of the composite material, the waste fabrics can also be classified according to their structure, such as optical microscope, cloth microscope, etc. For example, they can be classified into woven, knitted, non-woven, composite fabrics and other types.

[0059] Thus, waste fabrics of predetermined materials and predetermined structures, such as wool waste woven fabrics, can be obtained. In step S120, the waste fabrics used are waste fabrics of predetermined materials and predetermined structures, so that waste fabric layers of predetermined materials and structures can be obtained. This method is conducive to achieving the predetermined strength of the composite material, ensuring the consistency of the strength of the composite material, and thus facilitating the subsequent use of the composite material.

[0060] In some specific embodiments of the present invention, the method for preparing starch as a starch adhesive comprises:

[0061] S210, mixing water and an acidic reagent to obtain a mixed solution;

[0062] S220, mixing starch with the mixed solution to obtain a first mixed substance;

[0063] S230, mixing the first mixed substance with alum and / or glucose to obtain a second mixed substance;

[0064] S240, heating and boiling the second mixed substance to obtain a starch adhesive.

[0065] That is to say, the method for preparing starch into a starch adhesive mainly includes: first, preparing the required mass of water, acidic reagent (for example, sulfuric acid), alum and glucose according to the mass of starch; then, slowly introducing the acidic reagent into the water to form a mixed solution; then, adding the starch to the mixed solution and stirring until the mixture is uniform to form a thin paste to obtain a first mixed substance; then, adding alum and glucose to the first mixed substance and stirring until the mixture is uniform to obtain a second mixed substance; finally, heating and boiling the second mixed substance, and after heating and boiling for a predetermined time, standing and cooling to obtain the desired starch adhesive.

[0066] In this embodiment, the pH value can be adjusted by an acidic reagent, which can provide a suitable acidic environment for the gelatinization of starch and the formation of adhesives, which is beneficial to improving the viscosity and stability of the starch adhesive; the added alum can be used as a curing agent and thickener, which can effectively improve the stability and curing performance of the starch adhesive; the added glucose can increase the viscosity and water resistance of the starch adhesive, thereby effectively improving the structural strength of the composite material.

[0067] According to one embodiment of the present invention, the mixed solution is added to the starch in portions and stirred continuously during the whole process; and / or, stirred continuously during the heating of the second mixed substance.

[0068] In this embodiment, by adding the mixed solution in batches, the starch and the mixed solution are fully contacted and evenly mixed, which effectively prevents the starch agglomeration and uneven mixing caused by adding the mixed solution all at once, thereby significantly improving the uniformity and overall quality of the starch adhesive. In addition, continuous stirring during the heating of the second mixed substance ensures that the starch adhesive is uniformly gelatinized during the heating process, avoids local overheating or burning, ensures the quality and performance of the starch adhesive, and thus improves the reliability of the prepared composite material.

[0069] In some specific embodiments of the present invention, glycerin and salicylic acid alcohol solution are added to the second mixed substance.

[0070] Specifically, before or after heating the second mixed substance, glycerol can be added to the second mixed substance. The added glycerol can increase the flexibility and adhesiveness of the starch adhesive, thereby effectively improving the structural strength and impact resistance of the composite material.

[0071] Furthermore, before or after heating the second mixed substance, adding salicylic acid alcohol solution thereto can significantly enhance the bonding strength of the starch adhesive and effectively improve the structural strength of the composite material. In addition, the rapid volatilization of alcohol in the solution helps the starch adhesive to dry quickly, thereby shortening the preparation cycle of the composite material.

[0072] According to an embodiment of the present invention, the temperature for heating the second mixed substance is 50°C to 80°C.

[0073] When the temperature of heating the second mixed substance is insufficient, the starch adhesive may not be fully gelatinized, resulting in insufficient bonding strength and stability of the starch adhesive, affecting the final performance of the composite material; on the contrary, when the temperature of heating the second mixed substance is too high, it may cause excessive degradation or burning of the starch adhesive, which will also affect the performance of the composite material. In this embodiment, the temperature of heating the second mixed substance is 50°C to 80°C. Within this range, the starch adhesive can be fully gelatinized, thereby ensuring the bonding strength and stability of the starch adhesive, and avoiding excessive degradation or burning of the starch molecular chain caused by excessively high temperature, which can ensure the overall performance of the starch adhesive, and further ensure the structural strength and impact resistance of the composite material.

[0074] In some specific embodiments of the present invention, the weight ratio of the starch to the water is 1:2-7, the weight ratio of the starch to the acidic agent is 100:2-5, and the weight ratio of the starch to the alum is 100:10-30.

[0075] Specifically, the weight ratio of starch to water is 1:2-7, for example, 1:2, 1:3, 1:4, 1:5, 1:6 and 1:7, etc.; the weight ratio of starch to acidic agent is 100:2-5, for example, 100:2, 100:3, 100:4 and 100:5, etc.; the weight ratio of starch to alum is 100:10-30, for example, 100:10, 100:20 and 100:30, etc. When preparing the powder adhesive, the required mass of starch, water, acidic agent, alum and glucose can be prepared according to the above ratio range. Under the above ratio range, the overall performance of the starch adhesive can be guaranteed, and the structural strength and impact resistance of the composite material can be guaranteed.

[0076] In some optional examples of the present invention, the weight ratio of starch to water is 1:2, the weight ratio of starch to acidic agent is 100:2, and the weight ratio of starch to alum is 100:30. By adopting the above ratio range, the overall performance of the starch adhesive can be guaranteed, and the structural strength and impact resistance of the composite material can be guaranteed.

[0077] In some specific embodiments of the present invention, in the process of stacking the waste fabric layers layer by layer, the stacking direction of at least one layer of waste fabric is different from or the same as the stacking direction of the previous layer.

[0078] Specifically, fabrics have different weaving methods, which results in different weaving methods for the waste fabric layers obtained. For example, woven fabrics have a warp and weft structure, and their warp and weft properties are different. Knitted fabrics have a weft or warp structure, and their transverse and longitudinal properties are also different. When waste fabric layers with different warp and weft / transverse and longitudinal properties are stacked, the mechanical properties of the composite material can be optimized by changing the direction of the waste fabric layers when stacking, which is conducive to the strength of the composite material to reach a predetermined strength.

[0079] Therefore, in this embodiment, when stacking the waste fabric layers layer by layer, the stacking directions of the waste fabric layers can be configured as follows:

[0080] Case 1: The stacking direction of each layer of waste fabric is different from that of the previous layer;

[0081] Case 2: The stacking direction of each layer of waste fabric is the same as that of the previous layer;

[0082] Case 3: The stacking direction of some waste fabric layers is different from that of the previous layer, and the stacking direction of some waste fabric layers is the same as that of the previous layer.

[0083] In detail, when stacking the waste fabric layers, the stacking direction of the first layer of waste fabric layers is first determined, and then for each subsequent layer of waste fabric layers, the same or different stacking direction as the previous layer is selected according to predetermined design requirements.

[0084] It should be noted that different stacking directions can be but are not limited to 30 degrees, 45 degrees, 60 degrees, 75 degrees or 90 degrees relative to the direction of the previous layer of waste fabric layer. The specific stacking direction can be adjusted according to the mechanical properties required by the composite material so that the strength of the prepared composite material reaches the predetermined strength, which will not be repeated in this embodiment.

[0085] According to one embodiment of the present invention, the method of curing the preform to obtain a composite material includes: S410 and S420.

[0086] S410, applying pressure to the preform and allowing it to stand and solidify to form a solidified molded body;

[0087] S420, heating and drying the cured molded body to obtain a composite material.

[0088] That is to say, the method of curing the preform to obtain the composite material mainly includes: firstly placing a weight on the upper surface of the preform to apply a predetermined pressure to the preform, and then leaving it to stand at room temperature to cure for a predetermined time, such as about 12 hours, so as to obtain a cured molded body; then, placing the cured molded body in an electric constant temperature blast drying oven and drying it at a temperature of about 60°C for about 1 hour. After drying, the desired composite material can be obtained.

[0089] In this embodiment, by applying pressure to the preform, the starch adhesive in the preform can be evenly distributed and the preform can be effectively prevented from deforming during the curing process, which not only ensures the isotropy of the composite material, but also ensures the consistency of its mechanical properties.

[0090] According to one embodiment of the present invention, in the composite material, the content of the waste fabric layer is 79 wt.% to 91 wt.%.

[0091] That is to say, when the weight content of the waste fabric layer in the composite material is too high or too low, the impact resistance of the composite material will be affected. In this embodiment, the content of the waste fabric layer in the composite material is between 79wt.% and 91wt.%, within which the composite material can be guaranteed to have good impact resistance.

[0092] In some specific embodiments of the present invention, in the composite material, the content of the waste fabric layer is 87 wt.%.

[0093] When the weight content of the waste fabric layer in the composite material is lower than 87wt.% or higher than 87wt.%, its impact resistance is relatively low. In this embodiment, the weight content of the waste fabric layer in the composite material is configured to be 87wt.%, and this content makes the impact resistance of the composite material reach the best state. Therefore, the composite material prepared with this content can effectively improve the impact resistance of the composite material.

[0094] In some optional examples of the present invention, the starch includes one or more combinations of wheat flour, rice flour, corn flour, glutinous rice flour, sweet potato flour, and lotus root flour.

[0095] In this example, the starch adhesive prepared using wheat flour, rice flour, corn flour, glutinous rice flour, sweet potato flour, lotus root flour, etc. as the main raw materials can ensure that the product has the advantages of wide raw materials, renewable, environmentally friendly and cost-effective, and can ensure the reliability of the starch adhesive. The use of this starch adhesive can effectively improve the strength of the composite material, improve the flexibility of the composite material, thereby effectively improving the impact resistance of the composite material, allowing the composite material to withstand greater impact force.

[0096] The effect of the composite material of the embodiment of the present invention is described in detail below in conjunction with the experimental group.

[0097] Impact performance test method:

[0098] The impact performance of the composite material was tested using a drop hammer impact tester. The size of the impact sample is 80mm long and 80mm wide. During the test, the sample was fixed by a ring fixture with an inner diameter of 40mm. The diameter of the striker used in the test was 16mm and had a mass of 0.239kg. The hemispherical head of the striker has a mass of 0.632kg, a counterweight mass of 1kg, a total length of the punch assembly of 340mm, a total drop weight of 4.371kg when the impact energy is less than 40J, and a total drop weight of 8.371kg when the impact energy is 40J. During the test, the impact point is located at the center of the sample. The impact energies selected are 5J, 10J, 15J, 20J, 30J, and 40J, and the corresponding impact velocities are 1.51m / s, 2.12m / s, 2.58m / s, 2.94m / s, 3.57m / s, and 3.05m / s, respectively.

[0099] When the content of the waste fabric layer in the composite material is 79wt.% to 91wt.%, the composite material does not break after being impacted by an impact energy of 30J. Figure 2 It can be seen that the composite material has good impact resistance, especially when the content of the waste fabric layer in the composite material is 87wt.%, the impact resistance of the composite material reaches a peak value.

[0100] When the content of the waste fabric layer in the composite material is 87wt.%, the composite material does not break after being impacted by 5J, 10J, 15J, 20J, 30J, and 40J impact energies. Figure 3 It can be seen that the relationship between force and time, and energy and time of the composite material has the same trend when the impact test is carried out with different impact energies. With the increase of impact energy, the peak force and maximum energy both show an obvious increasing trend. When the impact capacity is 40J, the peak force of the composite material is 4270N and the maximum energy is 39.72J. This shows that the composite material can absorb more energy and withstand greater impact force under high impact energy. This is because after the starch adhesive is compounded with the wool fabric, the interface friction between the fibers, yarns, and cloth layers in the fabric structure increases the absorption of the composite material to the impact energy, thereby effectively improving the impact resistance of the composite material.

[0101] In summary, according to the preparation method of the composite material of the embodiment of the present invention, the waste fabric layer is used as the base material of the composite material, so that the waste fabric is recycled and reused, the waste of resources is reduced, and it is in line with the concept of circular economy. This not only reduces the demand for new raw materials, but also reduces the pressure on the environment caused by waste fabrics, and can achieve high-value reuse of waste fabrics. In addition, the use of starch adhesive as an adhesive for bonding waste fabric layers can greatly reduce the production cost of the composite material, making it more suitable for large-scale production, and increase the weight content of the fabric in the composite material, thereby reducing the weight of the composite material; and effectively improve the strength of the composite material, improve the flexibility of the composite material, thereby effectively improving the impact resistance of the composite material, so that the composite material can withstand greater impact force; at the same time, the green and environmentally friendly characteristics of the starch adhesive also enhance the environmental protection of the composite material.

[0102] The embodiment of the present invention further provides a composite material, which is made by the method for preparing the composite material described in any of the above embodiments. Since the method for preparing the composite material according to the embodiment of the present invention has the above technical effects, the composite material according to the embodiment of the present invention also has the corresponding technical effects, which will not be described in detail in this embodiment.

[0103] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. A method for preparing a composite material, characterized in that: include: Obtain scrap fabric layers; preparing starch into starch adhesive; Laying the waste fabric layers layer by layer to a preset thickness, and allowing the starch adhesive to penetrate each of the waste fabric layers to obtain a preform; The preform is cured to obtain a composite material.

2. The preparation method according to claim 1, characterized in that: The method for obtaining the waste fabric layer comprises: Wash and dry waste fabrics; The waste fabric is cut into a predetermined size to obtain a waste fabric layer.

3. The preparation method according to claim 2, characterized in that: Before cutting the waste fabric, the material and / or structure of the waste fabric is detected, and waste fabric of predetermined material and / or structure is screened out according to the detection result, and the waste fabric of predetermined material and / or structure is cut to a predetermined size to obtain a waste fabric layer.

4. The preparation method according to claim 1, characterized in that: The method for preparing starch as a starch adhesive comprises: Mixing water and an acidic reagent to obtain a mixed solution; Mixing starch with the mixed solution to obtain a first mixed substance; mixing the first mixed substance with alum and / or glucose to obtain a second mixed substance; The second mixed material is heated and boiled to obtain a starch adhesive.

5. The preparation method according to claim 4, characterized in that: The mixed solution is added to the starch in portions and stirred continuously during the whole process; and / or the second mixed substance is heated and stirred continuously.

6. The preparation method according to claim 4, characterized in that: Glycerin and salicylic acid alcohol solution are added to the second mixed material.

7. The preparation method according to claim 4, characterized in that: The temperature at which the second mixed substance is heated is 50°C to 80°C.

8. The preparation method according to claim 4, characterized in that: The weight ratio of the starch to the water is 1:2-7, the weight ratio of the starch to the acidic agent is 100:2-5, and the weight ratio of the starch to the alum is 100:10-30.

9. The preparation method according to claim 1, characterized in that: In the process of stacking the waste fabric layers layer by layer, the stacking direction of at least one layer of waste fabric is different from or the same as the stacking direction of the previous layer.

10. The preparation method according to claim 1, characterized in that: The method of curing the preform to obtain a composite material comprises: Applying pressure to the preform and allowing it to stand and solidify to form a solidified molded body; The cured molded body is heated and dried to obtain a composite material.

11. The preparation method according to claim 1, characterized in that: In the composite material, the content of the waste fabric layer is 79wt.% to 91wt.%.

12. The preparation method according to claim 1, characterized in that: In the composite material, the content of the waste fabric layer is 87 wt.%.

13. The preparation method according to claim 1, characterized in that: The starch includes one or more combinations of wheat flour, rice flour, corn flour, glutinous rice flour, sweet potato flour and lotus root flour.

14. A composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 13.